1991
DOI: 10.1002/gepi.1370080405
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of human plasma dopamine‐β‐hydroxylase thermal stability

Abstract: Although the structural gene for human dopamine-beta-hydroxylase (DBH) has been cloned, the mechanism by which DBH physical properties and activity are regulated is not well understood. Previous reports have suggested that three-allele or two-locus models may account for the genetic regulation of these traits in human blood. It is an interesting challenge to determine the extent to which quantitative analyses will complement or guide molecular genetic studies. In this study we analyzed data on the physical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
0
5
1
Order By: Relevance
“…It is localized to chromosome 9q34, closely linked to the ABO blood group and arginosuccinate synthetase loci (theta = 0) [Perry et al, 1991;Wilson et al, 19881. Plasma DPH levels are genetically controlled and stable over time in older children and adults [Faraone et al, 1994;Vuchetich et al, 1991;Weinshilboum, 1983;Weinshilboum et al, 19731. Through feedback inhibition, norepinephrine inhibits tyrosine hydroxylase, which in turn inhibits the production of dopamine and norepinephrine [Anden et al, 1973;Axelrod and Weinshilboum, 19721. In experimental animals, the inhibition of DPH activity results in a decrease in norepinephrine levels which releases the inhibition of tyrosine hydroxylase resulting in the excessive production of dopamine.…”
Section: Dopamine P-hydroxylasementioning
confidence: 99%
“…It is localized to chromosome 9q34, closely linked to the ABO blood group and arginosuccinate synthetase loci (theta = 0) [Perry et al, 1991;Wilson et al, 19881. Plasma DPH levels are genetically controlled and stable over time in older children and adults [Faraone et al, 1994;Vuchetich et al, 1991;Weinshilboum, 1983;Weinshilboum et al, 19731. Through feedback inhibition, norepinephrine inhibits tyrosine hydroxylase, which in turn inhibits the production of dopamine and norepinephrine [Anden et al, 1973;Axelrod and Weinshilboum, 19721. In experimental animals, the inhibition of DPH activity results in a decrease in norepinephrine levels which releases the inhibition of tyrosine hydroxylase resulting in the excessive production of dopamine.…”
Section: Dopamine P-hydroxylasementioning
confidence: 99%
“…Oligogenic inheritance accounts for almost all of the large interindividual variation in serum DβH levels in humans (Weinshilboum 1978;Elston et al 1979;Goldin et al 1982;Goldin 1985;Vuchetich et al 1991). Linkage studies employing phenotypic markers demonstrated that a major gene influencing serum DβH levels is linked to the ABO locus (Goldin et al 1982;Wilson et al 1988Wilson et al , 1990.…”
Section: Introductionmentioning
confidence: 95%
“…The gene (DBH) is closely linked to the ABO blood group on chromosome 9q34. Enzyme activity in serum or plasma is a stable, highly heritable, biochemical phenotype, 17 and as the major genetic determinant of serum D␤H is also linked to ABO, it suggests that DBH is a QTL for D␤H activity. We have used a TaqI polymorphism in the 5th intron in the present study.…”
mentioning
confidence: 99%